2016
DOI: 10.4103/0366-6999.179800
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minimal Skin Incision Technique in Living Kidney Transplantation and Conventional Kidney Transplantation

Abstract: Background:Recently, the most common incision for kidney transplantation (KT) is an inverted J-shaped incision known as the “hockey-stick.” However, demands for minimally invasive surgery in KT are increasing as in other various fields of surgery. Hence, we evaluated whether there is difference between minimal skin incision technique in kidney transplantation (MIKT) and conventional KT (CKT).Methods:Between June 2006 and March 2013, a total of 452 living kidney transplant patients were enrolled. The MIKT group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…MIKT, using a 7–9 cm transverse incision, 3–5 cm above the inguinal ligament, was first described in 21 kidney transplants by Oyen in 2006 ( 6 ). Kim ( 5 ), Kacar ( 9 ), and other similar series published later confirmed that MIKT is feasible and safe ( 10 ). Although there are few publications about MIKT in adults, we believe that SMIPKT is feasible and a more obvious choice for several reasons.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…MIKT, using a 7–9 cm transverse incision, 3–5 cm above the inguinal ligament, was first described in 21 kidney transplants by Oyen in 2006 ( 6 ). Kim ( 5 ), Kacar ( 9 ), and other similar series published later confirmed that MIKT is feasible and safe ( 10 ). Although there are few publications about MIKT in adults, we believe that SMIPKT is feasible and a more obvious choice for several reasons.…”
Section: Discussionmentioning
confidence: 76%
“…Despite some limitations in space in obese patients using the small incision technique, there is no drawback in performing the anastomoses in overweight patients up to a BMI of 30 kg/m 2 in Claas Brockschmidt's and >30 kg/m 2 in Oyen's report ( 4 , 6 ). However, in a subsequent study by Kim, a BMI <25 kg/m 2 was the inclusion criterion for MIKT recipients to ensure adequate exposure to the surgical field ( 5 ). Although SMIPKT has been proven successful in pediatric candidates with a BMI >25 kg/m 2 in our transplantation center, it should be noted that the majority of pediatric candidates in our group were lean, with a BMI of <20 kg/m 2 , which was much lower than the previously described results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimally invasive surgery (MIS) has gained its popularity in many specialties in the last two decades or so, due to its minimal invasion, fewer complications, quick recovery, and the reduced expense. [234] In the field of orthopedic trauma, minimally invasive reduction and fixation, which is the ultimate goal that patients and surgeons have been in persistent pursuit of for a long time, has been achieved, benefiting from sustained attention and the emerging of various new concepts and techniques. Among them, biological osteosynthesis (BO) is one of the currently and widely applied concepts in the management of orthopedic trauma.…”
mentioning
confidence: 99%